Conceptualizing the relationship between Big Data Adoption (BDA) factors and Organizational Impact (IO)/ Hasnah Hashim, Farrah Diana Saiful Bahry and Mohd Sazili Shahibi - Hashim, Hasnah; Saiful Bahry, Farrah Diana; Shahibi, Mohd Sazili (Faculty of Information Management, 2021)
With concern to the growing and limited number of studies in Big Data impact for Malaysia context, this paper proposes a framework linking Big Data Adoption (BDA) factors and organizational impact (OI). The independent variables adapting Technology-Organization-Environment (TOE) Model, operationalized the three contexts comprises technology, organization, and environment. The organization dimension further refers to relative advantage, security and privacy, complexity and compatibility. The organization dimensions cover on skills, top management support, financial readiness and firm size. The third dimension that is the environment consists of competitive pressure, government support and market turbulence. This study focused on the correlational between Big Data adoption factors and OI specifically productivity, cost savings and innovation. The proposed framework is most appropriate to be studied using survey research at the firm or organizational level as the unit of analysis.